Logística reversa : estudo sobre o corpo do conhecimento e diagnóstico sobre o processo de reciclagem em uma indústria de compressores - Milano, Camila Bonelli de (2016)
environmental impacts in: production processes, buying and selling materials and return of the products or components to the supply chain. Motivated by the demand of environmentally aware consumers, raw material dearth, more restrictive legislation or by environmental marketing and seek for improved image towards competitors, companies have spent more time, money and staff in research and machinery towards a more sustainable productivity. Among the innovations and new tools, Reverse Logistics (RL) is the one responsible for the return of materials to the supply chain, adding value and importance to the components that go back into the production cycle, in order to become pieces, materials, new products or renewed ones, with its lifespan extended. First of all, before any performance or diagnostic activities, it is necessary to know the acquaintance such as definitions, accounts, methods and applications on the subject. Through literature review on relevant books and articles it was possible to list authors and titles of interest to subsidize the reader's insertion in the research field, in this case, to RL. This inventory helped the literature review, the case study and the composition of significant information. The case study consisted of a compressor’s recycling process in which a company product collection (within warranty), showing failure or non-functioning, were recovered to disassemble and forwarding of materials back in the supply chain. The work has three important results: first, it found that the RL company, although still at an early stage, allows the return of product-composing pieces avoiding direct disposal in landfills or dumps, returning them to the compressors supply chain or other ones, and this case study showed that RL has financial advantages. However, the second result shows that for the process to be considered RL some proceedings would need to be added, such as recovery of materials out of the warranty period (reducing the quantity of recycled products that would be inappropriately managed), innovation in procedures for collecting these materials, expanding the network of collection for sites near the company. These aspects analyzed need support by senior administration to be realized. The partnership between the University (researcher) and business (managers responsible for processes) provided the third result that was developed during the research material for questions and gathering information needed to compose and monitor the RL process on the organization. These questions were worked into five groups (guidelines) responsible for covering all the return chain of materials, including information about the stakeholders involved in the delivery of the material, processing and subsequent sale so that shared responsibility is inserted on the continuous process improvement. Finally, it concludes that the RL acquaintance is in constant development and change and it needs to be explored in all its possibilities to develop new techniques and methodologies which are capable of being applied in the supply-chain. RL is a promising, exciting and challenging tool and every new research will be responsible for contributing to the dynamism of its evolution.